Costs of Oral Complications of Cancer Therapies: Estimates and a Blueprint for Future Study - Elting, Linda S; Chang, Yu-Chia (Journal of the National Cancer Institute. Monographs, 2019)
Oral complications of cancer treatment are common; however, their clinical and economic importance is often underappreciated. We reviewed the literature on the economic implications of oral complications, updating a previous report in the predecessor to this issue. We searched the Medline and Scopus databases for papers published as of December 31, 2017 that described the economic consequences of preventing and managing oral complications and reviewed the literature reporting the costs of oral mucositis, xerostomia, and osteonecrosis. Cost estimates were inflated to 2017 US dollars. We identified 16 papers describing the cost of managing mucositis, eight describing the cost of osteoradionecrosis, one describing the cost of bisphosphonate-associate osteonecrosis of the jaw, and four describing the cost of xerostomia. The incremental cost of oral mucositis was approximately $5000-$30 000 among patients receiving radiation therapy and $3700 per cycle among patients receiving chemotherapy. The incremental cost of mucositis-related hospitalization among stem cell transplant recipients exceeded $70 000. Conservative management of osteoradionecrosis (antibiotics, debridement) costs $4000-$35 000, although estimates as high as $74 000 have been reported. Hyperbaric oxygen therapy may add $10 000-$50 000 to the cost of therapy. Sialogogues are required for years for the management of xerostomia at a cost of $40-$200 per month. Serious (hospitalization, hyperbaric oxygen therapy) or long-term (sialogogues) outcomes are the major drivers of cost. Future research should address patients' out-of-pocket costs and the costs of oral complications of new treatments. Multisite studies, particularly those conducted by cooperative groups, should be prioritized.